Amyloid-bodies in the evolution of malignancies - Alexander Michael Grunfeld; Michael Bokros; Karelia Paz; Daniel Bilbao; Stephen Lee (PLoS ONE, 2026)
Tumorigenesis depends on the capacity for cancer cells to survive in the presence of various environmental stressors. An emerging paradigm in the study of cancer cell stress responses is their regulation by membrane-less intracellular compartments known as biomolecular condensates. While there has been considerable progress in our understanding of biomolecular condensates in cancer in vitro , a paucity of evidence remains for their presence and function in settings which more closely reflect in vivo tumor physiology. In this study, we use human tissues and an in vivo orthotopic mouse model to study the role of the Amyloid-body, a stress-induced condensate, in tumorigenesis. We present methodology to visualize Amyloid-bodies in tumors by multiple immunohistochemical approaches in addition to a semi-automated analysis pipeline. Analysis of multiple tumor types reveals that Amyloid-bodies are detectable at all tumor grades and stages, to varying degrees, and negatively correlate with the cell proliferation marker Ki-67. Finally, in an orthotopic mouse model of breast cancer, we show that silencing long noncoding ribosomal intergenic spacer RNA (rIGSRNA) involved in Amyloid-body formation accelerates tumorigenesis in vivo . Together, these results suggest that Amyloid-body formation occurs in human cancers, further establishing the physiological relevance of biomolecular condensates.